Konsep dan Urgensi Konstitusi dalam Kehidupan Berbangsa dan Bernegara - Fedri Yani Wulandari; Afriliani Afriliani; Oza Salsa; Nurli Hayati; Bambang Trisno (Lembaga Pengembangan Kinerja Dosen, 2024)
The government of a country which has the power to regulate people's lives does not act arbitrarily, there is a regulatory system that regulates it. The control system describes a hierarchy or ranking from the highest level of rules to the lowest level of rules. The highest level of rules in a country is called the constitution. For this reason, it is necessary to strengthen knowledge about the concept and urgency of this institution in national and state life. The research method used was a literature review. By collecting library data and information by exploring knowledge or knowledge from sources such as books, journals, written works, lecture notes and several other sources that are related to the research object. The research results show that the Constitution is the implementation of legal rules in the relationship between society and government. Constitutionalism creates a situation that can increase feelings of security due to restrictions on previously established government authority. There are three views on the role of the constitution in national and state life, namely: The first view assumes that every country has a constitution, but the constitution should not be seen as everything. The second view assumes that the constitution is nothing more than the basic rules of the state in administering the state, and that the most important thing for the state is honest, authoritative and law-abiding state administration. The third view assumes that the constitution does not play a significant role in state life.